Essential Oils and Mindfulness Exercises in Influencing Gene Expression Involved in Mild Cognitive Impairment (MCI): A Systematic Review - Vania Joceline Santoso; Azminah Azminah (Green Publisher Indonesia, 2024)
Mild Cognitive Impairment (MCI) represents a transitional stage between normal cognitive function and dementia, affecting memory and other cognitive abilities. This systematic review explores the impact of essential oils and mindfulness exercises on gene expression involved in MCI. Despite the prevalence of pharmacological treatments, they offer limited prevention of MCI progression to dementia. Non-pharmacological interventions, such as mindfulness exercises, have demonstrated cognitive benefits, albeit with moderate efficacy. Essential oils, used in aromatherapy, show promise in supporting cognitive improvement through their impact on amyloid-beta and cholinesterase pathways. This review synthesizes findings from multiple studies between 2017 and 2024, highlighting that combining essential oils and mindfulness exercises may offer enhanced therapeutic outcomes for individuals with MCI. Further research is needed to establish the efficacy of this integrative approach, which could slow the progression of MCI and improve patients' quality of life.